Kiprah Rachma Saloh dalam“Wahana Budaya Nusantara”di Belanda - Laras Aridhini (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2020)
In globalized era nowadays, local culture should be preserved as the identity of the nation. Now, local culture can be presented through social media without diminish the value implied in it. Dance is one of the complex forms of performing arts. It is not like ‘non-performing music’ that can be enjoyed while doing other activities. Dance and other performing arts require more time and attention for a person to enjoy it because it requires a dimension of space and time (Irianto, 2017). Wahana Budaya Nusantara (WBN) is an art group that always attracts Dutch people to love Indonesian culture. Rachma Saloh is an empowered woman figure who is also an individual agency that pioneers and develops Indonesian culture through WBN. WBN needs to be discussed in this essay so that readers (especially Indonesians) love Indonesian culture more. In addition, a figure like Rachma should be exemplified for the preservation of culture. This essay used participant observation and onlineinterview to collect the data. Literature study was used as the analysis method. WBN was formed from Rachma’s ideas and developed with a small number of members. WBN performances are always eagerly awaited in every festivaland several semi-private events. Learning process is always performed by all members of WBN, hence all such members get the message that no late for starting to learn new thing.